A Phase II Study of the Combination of Oxaliplatin, Capecitabine, and Trastuzumab and Chemoradiotherapy in the Adjuvant Setting in Operated Patients With HER2-positive Gastric or Gastroesophageal Junction Cancer (TOXAG Study) A Turkish Oncology Group Study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Background: Trastuzumab prolonged the overall survival in patients with advanced gastric cancer with human epidermal growth factor receptor 2 (HER2) overexpression in combination with chemotherapy. In this phase II open-label prospective study, the tolerability and safety of trastuzumab with chemotherapy, and chemoradiotherapy for curatively resected patients with HER2-positive gastric carcinoma was investigated. Methods: The patients with HER2-positive gastric, or gastroesophageal junction adenocarcinoma, after gastrectomy plus D2 dissection, were included. They received 3 cycles of oxaliplatin (100 mg/m(2) intravenously day 1) plus capecitabine (850 mg/m(2) orally days 1 to 14), trastuzumab (8 mg/kg intravenously day 1 in cycle 1, 6 mg/kg thereafter) every 21 days, followed by chemoradiotherapy. Trastuzumab was given for 1 year. Results: Of the 212 patients screened, 35 were eligible, and 34 were treated. The median age was 56 years (minimum to maximum: 35 to 75 y), male patients constituted 73.5% (n=25), and 33 (97.1%) had gastric adenocarcinoma. R0 resection was performed in 30 (88.2%). The majority (26, 61.7%) were in stage III disease. Most of the adverse events were grade I/II, the most frequent grade III side effects were nausea (3, 8.8%), vomiting (3, 8.8%), diarrhea (2, 5.9%), and weight loss (n=2, 5.9%). Two patients died during the first 3 cycles of chemotherapy and chemoradiotherapy; 1 secondary to pulmonary thromboembolism, and the other due to cerebral ischemia. After excluding 2 with early progression and 1 consent withdrawal, of the remaining 31 patients, 28 (90.3%) were able to complete the chemotherapy and chemoradiotherapy part of the trial. After the 25 months follow-up period, 21 patients (61.8%) were alive. Overall survival at 12 and 24 months was 75.0% and 58.0%, while disease-free survival at 12 and 24 months was 65.7% and 55.0%, respectively. Conclusions: Trastuzumab in combination with capecitabine, oxaliplatin following chemoradiotherapy as the adjuvant therapy for gastric or gastroesophageal junction adenocarcinoma was considered as safe and tolerable. The frequency of HER2 overexpression in curatively resected patients is comparable to that in patients with metastatic disease
Keywords: gastric; gastroesophageal; HER2; trastuzumab; gastrectomy; D2 dissection; SURGERY; CHEMOTHERAPY